Educational and Health Services in the City of Safwan: A Study in Urban Geography - Hindi Jabir , Researcher. Maha; Sami Abdulaziz Al Qatrani , Lect. Dr. Firas (Basra studies journal, 2023)
The current research deals with studying the educational and health services in terms of their geographical distribution and evaluation of the efficiency of their service performance in the city of Safwan. The research included two main axes for this study. All its details and the statement of its service efficiency, based on the standards adopted by the planning organizing committees in Iraq, which showed that educational institutions in the city of Safwan are not distributed in a balanced manner consistent with the number of residents of the existed residential neighborhoods. In addition, the low level of efficiency of educational services, which was reflected in the personal impression of the heads of families, and the percentage of those who agreed that the level of performance of educational services was below the acceptable conditions. The percentage reached 78.1% of the total number of housing units in the city. Also the it was clear the absence of a hospital in the city of Safwan which was limited to only one primary health care center that provides services to the residents of the city and its region.